STATUS OF SOCIOLINGUISTIC COMPETENCE WITHIN MODELS OF COMMUNICATIVE COMPETENCE - Xamroyeva Nilufar Xamidullaevna (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
In today's globalized society, the ability to express oneself in a foreign or second language is a vital skill. For a speaker to be able to be considered a bilingual speaker, he or she must have the capability to talk about any subject in any situation from the dinner table to a speech at the inaugural ball. According to the American Council on the Teaching on foreign Languages (ACTFL) scale for language proficiency, superior level of speaking means the learner is approaching such a capacity. To reach the superior level of speaking ability, one must be able to speak about abstract topics and speak appropriately in a wide variety of settings with very few errors. However, even after studying another language for many years, learners often still never achieve this level of proficiency and have great difficulty in expressing themselves in that language to a native speaker. Reasons for this continued difficulty in communicating in the second language can include problems with pronunciation, lack of knowledge on actual speech use of idiomatic expressions and slang, and learner differences in the ability to acquire language and in motivation to produce native-like speech. Another important contributing factor for incompetence in the language is that the speaker does not know which utterances are appropriate in the social situation in which he or she is speaking. This ability to adjust one's speech to fit the situation in which it is said is called sociolinguistic competence, and without this ability, even the most perfectly grammatical utterances can convey a meaning entirely different from that which the speaker intended.